PROBABILITY MATHEMATICAL MODEL OF CRYSTALLIZATION OF BINARY ALLOY AT POURING OF STEEL - Ju. A. Samojlovich; V. I. Timoshpolskij; S. M. Kabishov (Литьë и металлургия, 2008)
The critical analysis of some modifications of quasiequilibrium model, which gained ground in computing practice at calculations of ingots consolidation, is carried out. Probability model of crystallization of binary alloy at pouring of steel is offered.